Estudio de prefactibilidad para la producción artesanal de pescado salado en la parroquia de Santa Rosa, cantón Salinas, provincia de Santa Elena - Balladares León, Mario Stalin (2018)
The present work carries out a pre-feasibility study for the artisan production of salted fish in the parish of Santa Rosa; where several factors are exposed that serve to determine the current state of this production and promote the creation of a small company that brings together all the producers of the aforementioned goods. Through the use of a descriptive research approach, it has been concluded that the production of salted fish has a fairly strong infraction in Santa Rosa's economy. This last inference has been determined because the activity that has been most done is that of the producers of the parish. In addition, according to the information gathered, it is found that the inhabitants of Santa Rosa are fully trained, because they have been familiar with the production of salted fish…….